2021
DOI: 10.3389/fonc.2021.643375
|View full text |Cite
|
Sign up to set email alerts
|

Mutated DNA Damage Repair Pathways Are Prognostic and Chemosensitivity Markers for Resected Colorectal Cancer Liver Metastases

Abstract: Deficiency of the DNA damage repair (DDR) signaling pathways is potentially responsible for genetic instability and oncogenesis in tumors, including colorectal cancer. However, the correlations of mutated DDR signaling pathways to the prognosis of colorectal cancer liver metastasis (CRLM) after resection and other clinical applications have not been fully investigated. Here, to test the potential correlation of mutated DDR pathways with survival and pre-operative chemotherapy responses, tumor tissues from 146 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In the genomic analysis of 137 CRLM patients’ tumor tissues by Wang Kun et al. ( 16 ), defects in DNA damage repair signaling pathways such as MMR were found to have a significant negative impact on the overall survival of patients. dMMR in particular was found to be a significant indicator for OS in patients with colorectal cancer after surgical treatment in the study of Wen-Yue Yan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the genomic analysis of 137 CRLM patients’ tumor tissues by Wang Kun et al. ( 16 ), defects in DNA damage repair signaling pathways such as MMR were found to have a significant negative impact on the overall survival of patients. dMMR in particular was found to be a significant indicator for OS in patients with colorectal cancer after surgical treatment in the study of Wen-Yue Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete or partial expression of MMR protein is more likely to cause intrahepatic recurrence (15). In the genomic analysis of 137 CRLM patients' tumor tissues by Wang Kun et al (16), defects in DNA damage repair signaling pathways such as MMR were found to have a significant negative impact on the overall survival of patients. dMMR in particular was found to be a significant indicator for OS in patients with colorectal cancer after surgical treatment in the study of Wen-Yue Yan et al (17), who found that patients with dMMR also had longer PFS and OS compared to those with pMMR.…”
Section: Discussionmentioning
confidence: 99%
“… 34 A further implication of the impact of genomic instability on antitumor immunity in CRC is that many chemotherapeutic treatments currently in clinical use to treat CRC, such as the FOLFOX or FOLFIRI regimens, induce DNA damage that can activate the cGAS/STING pathway. 35 38 This implies that combinatorial treatments of chemotherapeutic regimens or radiotherapy with immune checkpoint inhibitors (ICIs) could potentially improve the prognosis of many CRC patients. 39 …”
Section: The Impact Of Genomics On Crc Immunotherapymentioning
confidence: 99%